Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1973
DOI: 10.2307/3896466
|View full text |Cite
|
Sign up to set email alerts
|

Plant Induced Soil Salinity Patterns in Two Saltbush (Atriplex spp.) Communities

Abstract: Highlight: A detailed examination was made into the soil the arid and semi-arid regions of Australia (Leigh and Noble, salinity distribution of two Atriplex communities, A. vesicaria and A. nummularia, established at regular spacings on two soil 1969) and other parts of the arid world. They are tolerant to types. The results based on total soluble salts and chloridesdrought and salinity and have high salt content in their leaves suggested that both saltbush species induced significantly (Wood, 1925;Beadle et a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
27
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 3 publications
(2 reference statements)
7
27
0
1
Order By: Relevance
“…It was not specified whether the inhibition of native species by Na was caused by increased osmotic potential (salinity) or ion substitution (metal toxicity). Although Sharma and Tongway (1973) were able to demonstrate that an increase in soil salinity was caused by the shrub Atriplex nummularia, the conclusion that this was responsible for the lack of vegetation in the understory, which was not supported by empirical evidence. Confounding factors were not considered, such as the effects from grazing, resource competition, or organic allelopathic compounds.…”
Section: Saltsmentioning
confidence: 76%
See 2 more Smart Citations
“…It was not specified whether the inhibition of native species by Na was caused by increased osmotic potential (salinity) or ion substitution (metal toxicity). Although Sharma and Tongway (1973) were able to demonstrate that an increase in soil salinity was caused by the shrub Atriplex nummularia, the conclusion that this was responsible for the lack of vegetation in the understory, which was not supported by empirical evidence. Confounding factors were not considered, such as the effects from grazing, resource competition, or organic allelopathic compounds.…”
Section: Saltsmentioning
confidence: 76%
“…Isolate and characterize toxin Vivrette and Muller (1977), Morris et al (2006) Determine toxin levels found naturally in accumulator species, rates of deposition, and accumulation in soils Sharma and Tongway (1973), Vivrette and Muller (1977), Boyd et al (1999), Boyd and Jaffre (2001), Zhang et al (2005Zhang et al ( , 2007 Select proper bioassay based on Vivrette and Muller (1977), Lesica and Deluca (2004), Morris et al (2006) growth form species phenology Determine uptake and symptoms of the toxin in affected species Vivrette and Muller (1977), Morris et al (2006) Source: Adapted from Fuerst and Putnam (1983) Plant Ecol (2009) 202:1-11 5 which concentrate their roots at the soil surface, may be better candidates. For species which are thought to phytoenrich elements through acidification or other modifications of the rhizosphere, root architecture may not be as important.…”
Section: Criteria For Determining Elemental Allelopathymentioning
confidence: 99%
See 1 more Smart Citation
“…Ten (approx. 100 g) samples from inland areas (80 m from the nearest coast) per island were taken at a depth of 10 cm from areas with Atriplex (interplant spaces; Sharma and Tongway, 1973) and combined. Soils were analysed at the University of Arizona Soil Lab.…”
Section: Soil Chemistrymentioning
confidence: 99%
“…They are tolerant to drought and salinity and have high salt content in their leaves (Sharma and Tongway 1973;Wallace, Romney, and Mueller 1982;Soufi and Wallace 1982) and aerial parts (Sameni and Soleimani 2007). The leaves and aerial parts of these and similar plants, after falling to the ground, are likely to increase the salinity of soil beneath the plant (Sharma and Tongway 1973;Jessup 1969).…”
Section: Introductionmentioning
confidence: 99%